Polyimide varnish and polyimide coating material prepared therefrom

By adding nanosilicon dioxide to the polyimide varnish, the problem of insufficient pulse durability of the polyimide coating material under high voltage conditions is solved, and the effect of significantly improving the pulse durability and haze performance of the coating material is achieved.

CN119529663APending Publication Date: 2025-02-28PI ADVANCED MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411178843.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-28
Filing Date
2024-08-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Under high voltage conditions, the polyimide coating material is prone to partial discharge, resulting in deterioration of the coating of the insulating wire, thereby shortening the life of the electrical equipment and lacking excellent pulse durability characteristics.

Method used

By adding a certain range of nanosilicon dioxide to the polyimide varnish, the average particle size of the nanosilicon dioxide is 1000 nm or less and the moisture content is less than 0.5 wt%, to improve the pulse durability and haze performance of the coating.

Benefits of technology

The pulse durability and haze performance of polyimide coating materials are significantly improved, the life of electrical equipment is extended, and excellent insulation performance is maintained under high voltage conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005011501030000111
    Figure BDA0005011501030000111
  • Figure BDA0005011501030000121
    Figure BDA0005011501030000121
  • Figure BDA0005011501030000131
    Figure BDA0005011501030000131
Patent Text Reader

Abstract

Provided is a polyimide varnish comprising: a polyamic acid and nanosilica, in which the nanosilica accounts for 5 wt% to 23 wt% with respect to the solid content of the polyamic acid, and the nanosilica has a water content of less than 0.5 wt%.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority under 35 U.S.C. §119 to Korean Patent Application No. 10-2023-0113155 filed in the Korean Patent Office on August 28, 2023, the disclosure of which is incorporated herein by reference in its entirety. Technical Field

[0003] The following disclosure relates to a polyimide varnish and a polyimide coating material prepared therefrom, and more particularly, to a polyimide varnish having excellent pulse durability and a polyimide coating material prepared therefrom. Background Art

[0004] Polyimide resin refers to a high heat-resistant resin obtained by solution polymerization on aromatic dianhydride and aromatic diamine or aromatic diisocyanate to produce a polyamic acid derivative, followed by closed-loop dehydration and imidization at high temperature. Polyimide resin is an insoluble, non-meltable, ultra-high heat-resistant resin, and has excellent properties such as thermal oxidation resistance, heat resistance, radiation resistance, low temperature characteristics, chemical resistance, etc., so it is used in a wide range of fields, including heat-resistant advanced materials such as automotive materials, aviation materials and spacecraft materials, and electronic materials such as insulating coatings, insulating films, semiconductors and electrode protective films for TFT-LCD. Recently, polyimide resins are also used in display materials such as optical fibers and liquid crystal orientation films, transparent electrode films by including conductive fillers in the film or performing surface coating.

[0005] In particular, in insulated wires used as coil windings of motors, etc., the insulating layer (insulating film) coating the conductor needs to have excellent insulating properties, adhesion to the conductor, heat resistance, mechanical strength, etc. Therefore, polyimide is used as a resin to form the insulating layer.

[0006] However, in electrical devices with high applied voltage, such as motors used at high voltage, high voltage is applied to the insulating wire constituting the electrical device in the insulating layer or coating material, and there is still a need to develop polyimide having excellent pulse durability characteristics to handle such high voltage.

[0007] Specifically, local discharge (corona discharge) is likely to occur on the coating surface where high voltage is applied, and when the occurrence of corona discharge causes a local temperature rise or the generation of ozone or ions, the coating of the insulated wire may deteriorate, causing premature insulation breakdown and shortening the life of the electrical equipment. Therefore, the use of polyimide as a coating material for conductors, especially as a coating material for applying high voltage, requires improvement in pulse durability characteristics such as insulation breakdown voltage performance or corona discharge initiation voltage. Summary of the invention

[0008] One embodiment of the present invention is directed to providing a polyimide varnish having excellent physical properties such as pulse durability and haze by including a certain range of nano-silica having a certain range of water content.

[0009] Another embodiment of the present invention is directed to providing a polyimide cured product in which a polyimide varnish is cured.

[0010] Yet another embodiment of the present invention is directed to a polyimide coating material comprising a polyimide varnish.

[0011] The present invention can be modified in various ways and can implement various embodiments. However, these embodiments are not intended to limit the present invention to specific embodiments, and should be understood to include all modifications, equivalents and substitutes included in the spirit and scope of the present invention.

[0012] The terms used in this application are only used to describe specific embodiments and are not intended to limit the present invention. Unless the context clearly indicates otherwise, singular expressions include plural expressions. In this specification, terms such as "comprises / includes / contains (comprise)" or "have (have)" are intended to indicate the presence of features, numbers, steps, operations, components, parts or combinations thereof described in the specification, and should not be understood as excluding the presence or addition of one or more other features, numbers, steps, operations, components, parts or combinations thereof.

[0013] When amounts, concentrations or other values ​​or parameters are given herein as ranges, preferred ranges or lists of upper limits of desired values ​​and lower limits of desired values, it should be understood that all ranges formed by any pair of any upper range limit or preferred value and any lower range limit or preferred value are specifically disclosed, regardless of whether a range is disclosed individually.

[0014] Where numerical ranges are stated herein, it is intended that the endpoints of the range and the scope of the invention within that range are not limited to the specific values ​​stated when defining the range, unless otherwise indicated.

[0015] As used herein, "dianhydride" is intended to include its precursors or derivatives, also known as "dianhydride" or "acid dianhydride." These products may not technically be dianhydrides, but will still react with diamines to form polyamic acid, and the polyamic acid can be converted back to polyimide.

[0016] As used herein, "diamine" is intended to include precursors or derivatives thereof, which may not technically be diamines but will still react with the dianhydride to form polyamic acid, and the polyamic acid can be converted back to a polyimide.

[0017] In addition, unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as those generally understood by those of ordinary skill in the art to which the present invention belongs. Terms such as those defined in commonly used dictionaries should be interpreted as having the same meaning as in the context of the relevant technology, and unless clearly defined in this application, should not be interpreted in an idealized or overly formal sense. The specific details of the implementation of the present invention will be described below.

[0018] Polyimide varnish

[0019] In one general aspect, a polyimide varnish is provided that has improved pulse durability and is useful in conductor coating applications.

[0020] In one aspect of the present invention, a polyimide varnish is provided, comprising: polyamic acid and nano-silicon dioxide, wherein the nano-silicon dioxide accounts for 5wt% to 23wt% relative to the solid content of the polyamic acid, and the water content of the nano-silicon dioxide is less than 0.5wt%.

[0021] Nano Silica

[0022] The polyimide varnish of the present invention may contain nano-silica to improve physical properties such as pulse durability, etc., wherein the nano-silica is nano-scale silicon dioxide (SiO2) fine particles having an average particle diameter of 1000nm or less, and its form and shape are not particularly limited.

[0023] In addition, relative to the solid content of polyamic acid, the amount of nano silicon dioxide can be 5wt% to 23wt%. For example, the lower limit of the amount of nano silicon dioxide can be 5.5wt%, 6.0wt%, 6.5wt%, 7.0wt%, 8.0wt%, 9.0wt%, 10.0wt% or 11.0wt% or more. In addition, the upper limit of the amount of nano silicon dioxide can be 22.0wt%, 21.5wt%, 21.0wt%, 20.5wt%, 20.0wt%, 19.0wt%, 18.5wt%, 18.0wt%, 17.0wt%, 16.0wt%, 15.0wt%, 14.0wt%, 13.5wt% or 13.0wt% or less. When the amount of nano-silica is less than 5wt%, it cannot effectively improve the pulse durability; when the amount of nano-silica is greater than 23wt%, it is not desirable because its physical properties may be reduced. Here, the solid content of polyamic acid is the total amount of dianhydride monomer and diamine monomer used in the polymerization reaction.

[0024] In addition, nano silicon dioxide can have a water content less than 0.5wt%. For example, the lower limit of the water content of nano silicon dioxide can be 0.49wt%, 0.48wt%, 0.47wt%, 0.46wt%, 0.45wt%, 0.44wt%, 0.43wt% or 0.42wt% or less. In addition, the lower limit of the water content of nano silicon dioxide is not particularly limited, but can be greater than 0wt%, 0.01wt%, 0.05wt%, 0.10wt% or 0.15wt% or more. In addition, the water content of nano silicon dioxide is 0.5wt% or more, which is undesirable because it may affect the formation of polymer molecular weight, resulting in a reduction in physical properties. Nano silicon dioxide can be provided as a dispersion liquid dispersed in an organic solvent, wherein water content refers to the water content in the dispersion liquid in which the nano silicon dioxide is dispersed.

[0025] In addition, the water content of nano-silica can be measured by Karl Fischer method. Specifically, the water content can be measured by using the quantitative reaction of water in KS M 0034 sample with iodine and sulfur dioxide.

[0026] In addition, nano-silicon dioxide can have an average particle size of 1 nm to 200 nm, particularly, for example, 5 nm to 150 nm, 5 nm to 100 nm, 5 nm to 70 nm, 10 nm to 50 nm or 10 nm to 30 nm. The average particle size can be measured by equipment such as BET, SEM, zeta potential analyzer, etc.

[0027] The nano-silica may also be nano-silica surface-modified with organic silane.

[0028] The organosilane of the nano-silica surface modified with the organosilane may include one or more selected from the following: methyltrimethoxysilane, hexamethyldisiloxane, n-octyltrimethoxysilane, n-octyltriethoxysilane, isooctyltrimethoxysilane, dodecyltrimethoxysilane, octadecyltrimethoxysilane, propyltrimethoxysilane, n-hexyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-(methacryloxy)propyltriethoxysilane, 3-(methacryloxy)propylmethyldimethoxysilane, 3-(acryloxypropyl)methyldimethoxysilane, 3-(methacryloxy)propyldimethylethoxysilane, styrylethyltrimethoxysilane, phenyltrimethoxysilane, Ethoxysilane, triethoxy-p-tolylsilane, vinylmethyldiacetoxysilane, vinyldimethylethoxysilane, vinylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, vinyltriisopropoxysilane, vinyltriphenoxysilane, vinyltri-tert-butoxysilane, vinyltri(isobutoxy)silane, vinyltriisopropenoxysilane, vinyltri(2-methoxyethoxy)silane, N,N-diisopropylethylaminophenyltrimethoxysilane, glycidoxypropyltrimethoxysilane (GPTMS), 3-aminopropyltrimethoxy-silane (APTMS), phenyltrimethoxysilane (PTMS) and N-phenyl-3-aminopropyltrimethoxysilane (PAPTES).

[0029] In addition, the nano-silica with organosilane surface modification can be obtained by combining the compound containing at least one phenyl at the terminal and the compound containing at least one amine group, hydroxyl group, sulfydryl group or epoxy group at the terminal on the surface of nano-silica. Specifically, the compound containing at least one phenyl at the terminal can be phenyltrimethoxysilane (PTMS) and N-phenyl-3-aminopropyltrimethoxysilane (PAPTES). In addition, the compound containing at least one amine group, hydroxyl group, sulfydryl group or epoxy group at the terminal can be glycidoxypropyltrimethoxysilane (GPTMS) or 3-aminopropyltrimethoxysilane (APTMS).

[0030] Nano-silica surface-modified with organosilane can be prepared by surface-treating nano-silica with organosilane. For example, nano-silica can be obtained by heating organosilane under acidic or alkaline conditions and performing surface treatment for about 1 hour to 24 hours. In addition, surface modification can be achieved by other known methods, for example, mixing organosilane in a solvent and reacting at a temperature of 10°C to 100°C or 20°C to 60°C for 1 hour to 10 hours or 1 hour to 5 hours to obtain surface-modified nano-silica. In order to combine two or more compounds on the surface of nano-silica, each of the above methods can be performed.

[0031] The nano-silica surface-modified with organosilane of the present invention can prevent the agglomeration of inorganic particles in the polyimide varnish, and can enhance the interaction with the solid content (polyamic acid) due to the functional groups of the compound, thereby improving the dispersibility and compatibility.

[0032] Polyamic acid

[0033] In the present invention, the polyamic acid may include a dianhydride monomer and a diamine monomer as polymerization units.

[0034] The dianhydride monomer may include at least one selected from the group consisting of pyromellitic dianhydride (PMDA), biphenyltetracarboxylic dianhydride (BPDA), benzophenonetetracarboxylic dianhydride (BTDA), oxydiphthalic anhydride (ODPA), diphenylsulfone-3,4,3',4'-tetracarboxylic dianhydride (DSDA), bis(3,4-dicarboxyphenyl)sulfide dianhydride, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,3,3',4'-benzophenonetetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, paraphenylene Bis(trimer monoester anhydride), p-bisphenylene bis(trimer monoester anhydride), m-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, p-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, 1,3-bis(3,4-dicarboxyphenoxy)phthalic dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)phthalic dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)biphenyl dianhydride, 2,2-bis[(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride and 4,4'-(2,2-hexafluoroisopropylidene)diphthalic dianhydride.

[0035] Preferably, the dianhydride monomer may include at least one selected from pyromellitic dianhydride (PMDA), biphenyltetracarboxylic dianhydride (BPDA), and benzophenonetetracarboxylic dianhydride (BTDA), and more preferably, includes pyromellitic dianhydride (PMDA).

[0036] The diamine monomer may include at least one selected from the group consisting of 1,4-diaminobenzene (PPD), 4,4'-diaminodiphenyl ether (ODA), 2,2-diaminophenoxyphenyl propane (BAPP), m-phenylenediamine, 3,3'-dimethylbenzidine, 2,2'-dimethylbenzidine, 2,4-diaminotoluene, 2,6-diaminotoluene, 3,5-diaminobenzoic acid (DABA), 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl (m-tolidine), 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenylmethane, 3,3'-diaminobenzidine, 2,2 ... Carboxy-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, 4,4'-diaminobenzanilide, 3,3'-dimethoxybenzidine, 2,2'-dimethoxybenzidine, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone, 3,3'-diamino-4,4'-dichlorobenzophenone, 3,3'-diamino-4,4'-dimethoxybenzophenone Benzophenone, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 2,2-bis(3-aminophenyl)propane, 2,2-bis(4-aminophenyl)propane, 2,2-bis(3-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 3,3'-diaminodiphenyl sulfoxide, 3,4'-diaminodiphenyl sulfoxide, 4,4'-diaminodiphenyl sulfoxide, 1,3-bis(3-aminophenyl)benzene, 1,3-bis(4-aminophenyl)benzene, 1,4-bis(3-aminophenyl)benzene, 1,4-bis(4-aminophenyl)benzene, 1,3-bis(4-aminophenyl)benzene 1,3-bis(3-aminophenoxy)benzene (TPE-R), 1,4-bis(3-aminophenoxy)benzene (TPE-Q), 1,3-bis(3-aminophenoxy)-4-trifluorotoluene, 3,3'-diamino-4-(4-phenyl)phenoxybenzophenone, 3,3'-diamino-4,4'-bis(4-phenylphenoxy)benzophenone, 1,3-bis(3-aminophenylene sulfide)benzene, 1,3-bis(4-aminophenylene sulfide)benzene, 1,4-bis(4-aminophenylene sulfide)benzene, 1,3-bis(3-aminophenyl sulfone)benzene, 1,3-bis(4-aminophenyl sulfone)benzene, 1,4-bis(4-aminophenyl sulfone)benzene, 1,3-bis[2-(4-aminophenyl)isopropyl]benzene, 1,4-bis[2-(3-aminophenyl)isopropyl]benzene, 1,4-Bis[2-(4-aminophenyl)isopropyl]benzene, 3,3'-bis(3-aminophenoxy)biphenyl, 3,3'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, bis[3-(3-aminophenoxy)phenyl]ether, bis[3-(4-aminophenoxy)phenyl]ether, bis[4-(3)-aminophenoxy)phenyl]ether, bis[4-(4-aminophenoxy)phenyl]ether, bis[3-(3 bis[3-(4-aminophenoxy)phenyl]ketone, bis[4-(3-aminophenoxy)phenyl]ketone, bis[4-(4-aminophenoxy)phenyl]ketone, bis[3-(3-aminophenoxy)phenyl]sulfide, bis[3-(4-aminophenoxy)phenyl]sulfide, bis[4-(3-aminophenoxy)phenyl]sulfide, bis[4-(4-aminophenoxy)phenyl]sulfide, bis[3-(3-aminophenoxy)phenyl]sulfide, bis[4-(4-aminophenoxy)phenyl]sulfide, bis[3-(3-aminophenoxy)phenyl]sulfone, bis[3-(4-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[3-(3-aminophenoxy)phenyl]methane, bis[3-(4-aminophenoxy)phenyl]methane, bis[4-(3-aminophenoxy)phenyl]methane, bis[4-(4-aminophenoxy)phenyl]methane, 2,2-bis[3-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(4-aminophenoxy)phenyl]propane, 2,2 -bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[3-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane and 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane.

[0037] Specifically, the diamine monomer may include at least one selected from 1,4-diaminobenzene (PPD), 4,4'-diaminodiphenyl ether (ODA), 2,2-diaminophenoxyphenylpropane (BAPP), 1,3-bis(4-aminophenoxy)benzene (TPE-R), and more preferably, may include 4,4'-diaminodiphenyl ether (ODA).

[0038] The polyamic acid may include pyromellitic dianhydride (PMDA) and 4,4′-diaminodiphenyl ether (ODA) as polymerization units.

[0039] In the present invention, the ratio of pyromellitic dianhydride (PMDA) contained in the total dianhydride monomers may be 50 mol% or more, specifically 60 mol% or more, 70 mol% or more, 75 mol% or more, 80 mol% or more, 85 mol% or more, 90 mol% or more, 95 mol% or more, 99 mol% or more, or 100 mol% or more.

[0040] In addition, the ratio of 4,4'-diaminodiphenyl ether (ODA) included in the total diamine monomers may be 50 mol% or more, specifically 60 mol% or more, 70 mol% or more, 75 mol% or more, 80 mol% or more, 85 mol% or more, 90 mol% or more, 95 mol% or more, 99 mol% or more, or 100 mol% or more.

[0041] Based on the diamine monomer of 100mol%, polyamic acid of the present invention can include the dianhydride monomer of 95mol% to 105mol%.For example, the lower limit of dianhydride monomer can be 96mol% or more, 97mol% or more, 98mol% or more, 99mol% or more or 99.5mol% or more, and the upper limit of dianhydride monomer can be 104mol% or less, 103mol% or less, 102mol% or less, 101mol% or less or 100.5mol% or less.In embodiments, diamine monomer and dianhydride monomer can react with substantially equimolar amount.

[0042] In addition, the molar ratio of the dianhydride monomer to the diamine monomer may be 6:4 to 4:6, preferably 5.5:4.5 to 4.5:6.5, and more preferably 5:5.

[0043] In addition, polyamic acid can have a solid content of 10wt% to 50wt%. The lower limit of the solid content of polyamic acid can be, for example, 13wt% or more, 15wt% or more, 18wt% or more, 20wt% or more, 23wt% or more, or 24wt% or more, and its upper limit can be, for example, 48wt% or less, 45wt% or less, 43wt% or less, 40wt% or less, 38wt% or less, 35wt% or less, 33wt% or less, 30wt% or less, or 27wt% or less. By regulating the solid content of polyamic acid, the increase of viscosity can be controlled and the processing time in the curing process can be shortened.

[0044] Organic solvents

[0045] In the present invention, the polyimide varnish further contains an organic solvent, wherein the organic solvent is not particularly limited as long as it is an organic solvent in which the polyamic acid is soluble, but as an example, may be an aprotic polar solvent.

[0046] Specifically, the organic solvent may include at least one selected from the group consisting of N-methylpyrrolidone (NMP), N,N'-dimethylformamide (DMF), N,N'-diethylformamide (DEF), N,N'-dimethylacetamide (DMAc), dimethylpropionamide (DMPA), N,N-diethylacetamide (DEAc), dimethyl sulfoxide (DMSO), 3-methoxy-N,N-dimethylpropionamide (KJCMPA), p-chlorophenol, o-chlorophenol, γ-butyrolactone (GBL), diethylene glycol dimethyl ether, and naphthalene. Preferably, the organic solvent may be N-methylpyrrolidone (NMP), N,N'-dimethylformamide (DMF), N,N'-dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO), and the like.

[0047] The organic solvent can also include a modifier containing a hydroxyl group (OH) or an amine group (NH). Examples of the modifier containing a hydroxyl group (OH) or an amine group (NH) include ethylamine, triethanolamine, dimethylamine, trimethylamine, diethylenetriamine, ethylenediamine, tributylamine, pyridine, tetrahydropyrrole, methanol, ethanol, propanol, isopropanol, sec-butyl alcohol, tert-butyl alcohol, n-pentanol, isopentanol, hexanol, octanol, capryl alcohol, nonanol, decanol, undecanol, dodecanol, myristyl alcohol, hexadecanol, stearyl alcohol, allyl alcohol, crotyl alcohol, propargyl alcohol, ethylene glycol, propylene glycol, benzyl alcohol, phenol, etc. The modifier can control the reactivity by reacting with the dianhydride monomer.

[0048] Polyimide varnish

[0049] At a temperature of 30°C and 1s -1 The polyimide varnish may have a viscosity of 500 cP to 20,000 cP measured at a shear rate of 1.5 s. For example, the upper limit of the viscosity may be 20,000 cP, 15,000 cP, 10,000 cP or less. The lower limit of the viscosity is not particularly limited, but may be 1,000 cP, 1,200 cP, 1,500 cP or 1,800 cP or more. The viscosity may be measured using, for example, Haake's Rheostress 600, and may be measured at a shear rate of 1 / s, a temperature of 30 ° C, and a plate gap of 1 mm.

[0050] The polyimide varnish may have a haze of 1.5% or less. For example, the upper limit of the haze may be 1.4% or less, 1.3% or less, 1.2% or less, 1.1% or less, 1% or less, 0.9% or less, or 0.8% or less, and the lower limit is not particularly limited, but may be greater than 0%, 0.05% or greater, or 0.1% or greater. In an embodiment, the haze may be measured using HunterLab's equipment according to ASTM E308.

[0051] Polyimide varnish curing products and coating materials

[0052] In another aspect of the present invention, there is provided a polyimide cured product obtained by curing the polyimide varnish as described above, wherein the polyimide cured product may include a film-type polyimide cured product or a polyimide coating material.

[0053] The polyimide-cured product may have a haze of 1.5% or less. For example, the upper limit of the haze may be 1.4% or less, 1.3% or less, 1.2% or less, 1.1% or less, 1% or less, 0.9% or less, 0.8% or less, 0.7% or less, 0.6% or less, or 0.5% or less, and the lower limit thereof is not particularly limited, but may be greater than 0%, 0.05%, or greater, or 0.1% or greater. In an embodiment, the haze may be measured using a Hunter apparatus according to ASTM E308, wherein the polyimide may have a thickness of 20 ± 1.0 μm.

[0054] According to IEC-60851-5, the impulse durability of polyimide cured products is 300 minutes or more, which is the time that the insulating material withstands a certain voltage. The lower limit of the impulse durability can be, for example, 400 minutes or more, 500 minutes or more, 550 minutes or more, 600 minutes or more, 650 minutes or more, 700 minutes or more, 750 minutes or more, 800 minutes or more, 850 minutes or more, 900 minutes or more, 950 minutes or more, 970 minutes or more, 980 minutes or more, 1,000 minutes or more, 1,100 minutes or more, 1,200 minutes or more, 1,300 minutes or more, 1,400 minutes or more, 1,500 minutes or more, or 2,000 minutes or more. The upper limit of the impulse durability is not particularly limited, but can be 4,000 minutes or more. The pulse durability can be determined by attaching the polyimide coating material to a jig, applying an AC 1.5 kV voltage (at a frequency of 60 Hz), and measuring the time until a leakage current of 5 mA or more is detected. Here, the thickness of the polyimide cured product can be 26 ± 1.0 μm.

[0055] Furthermore, according to the present invention, by including a high content of nano-silica having a certain range of water content, the pulse durability characteristics can be improved.

[0056] In yet another aspect of the present invention, a polyimide coating material including a polyimide cured product is provided.

[0057] In an embodiment, a method of preparing a polyimide coating material may include coating a polyimide varnish on a surface of a conductor; and imidizing the polyimide varnish coated on the surface of the conductor.

[0058] The conductor may be a copper wire made of copper or a copper alloy, but may also include conductors made of other metal materials, such as silver wire, etc., or various plated metal wires, such as aluminum or tinned wires, etc. The thickness of the conductor and the coating material may conform to the KSC3107 standard. The diameter of the conductor may be in the range of 0.3 mm to 3.2 mm, and the standard film thickness of the coating film (the average value of the maximum film thickness and the minimum film thickness) may be: 21 μm to 194 μm for type 0, 14 μm to 169 μm for type 1, and 10 μm to 31 μm for type 2. Depending on the cross-sectional shape of the conductor, the conductor may have a circular, rectangular, hexagonal, etc. shape, but is not limited thereto.

[0059] In another aspect of the present invention, there is provided an electric wire comprising a polyimide coating material.

[0060] Specifically, the wire may be a coated wire comprising a polyimide coating material prepared by coating a polyimide varnish on the surface of the wire and then imidizing it. In an embodiment, the coated wire may include an electric wire; and a coating material, wherein the above-mentioned polyimide is coated on the surface of the wire and imidized.

[0061] Furthermore, the present invention can provide an electronic device comprising the coated wire. The electronic device can be, for example, an electric motor.

[0062] Furthermore, in yet another aspect, a component including a molded body formed of a polyimide varnish is provided.

[0063] Specifically, the components may include electronic circuit board components, semiconductor devices, lithium ion battery components, solar cell components, fuel cell components, motor windings, engine peripheral components, paints, optical components, thermal insulation materials, electromagnetic shielding materials, surge components, dental materials, sliding coatings, and electrostatic chucks. DETAILED DESCRIPTION

[0064] In order to facilitate the understanding of the present invention, the following examples are given. These examples are provided only to make it easier to understand the present disclosure, but the content of the present disclosure is not limited by these examples.

[0065] <Example>

[0066] Preparation Example 1: Nano-silica surface treated with organosilane

[0067] Nano-silica 1 (silica sol dispersed by dimethylacetamide, silica solid content concentration of 30wt%, silica average particle size of 10nm to 30nm, water content of 0.4wt%) was prepared with organic silane surface treatment. Here, the water content is the wt% of the total mass of the nano-silica dispersion liquid, and the water content of the nano-silica is measured by Karl Fischer method. Specifically, the water content is measured by quantitatively reacting the water in the KS M 0034 sample with iodine and sulfur dioxide.

[0068] Preparation Comparative Example 1. Nano-silicon dioxide

[0069] Nano-silica (silica sol dispersed by N-methylpyrrolidone, with a silica solid content concentration of 30 wt%, a silica average particle size of 10 nm to 20 nm, and a water content of 0.8 wt%) was prepared. Here, the water content is the wt% of the total mass of the nano-silica dispersion liquid, and the water content of the nano-silica is determined by the Karl Fischer method. Specifically, the water content is measured by using the quantitative reaction of the water in the KS M 0034 sample with iodine and sulfur dioxide.

[0070] Example 1. Polyimide varnish

[0071] Example 1-1

[0072] In a reaction vessel filled with nitrogen, an organic solvent containing dimethylacetamide (DMAc) and a modifier (0 mol% to 2 mol%) was added, and the nano-silica surface-treated with an organosilane (6 wt% relative to the polyimide solid content) according to Preparation Example 1 and pyromellitic dianhydride (PMDA) (92 mol%) as a dianhydride monomer were mixed and stirred at 40° C. for 30 minutes. Then, 4,4'-diaminodiphenyl ether (ODA) (100 mol%) and pyromellitic dianhydride (PMDA) (8 mol%) were added as diamine monomers, and stirred and polymerized at 40° C. for about 1 hour to prepare a polyimide varnish (polyimide solid content was 25 wt%).

[0073] Examples 1-2 to 1-7

[0074] A polyimide varnish was prepared in the same manner as in Example 1-1, except that the content of the nano-silica surface-treated with organic silane according to Preparation Example 1 was different, as described in Table 1 below.

[0075] Comparative Examples 1-1 to 1-2

[0076] A polyimide varnish was prepared in the same manner as in Example 1-1, except that the nano-silica prepared in Comparative Example 1 was used instead of the nano-silica surface-treated with organosilane in Example 1, and the content used was also different, as described in Table 1 below.

[0077] Comparative Examples 1-3 to 1-4

[0078] A polyimide varnish was prepared in the same manner as in Example 1-1, except that the content of the nano-silica surface-treated with organic silane according to Preparation Example 1 was different, as described in Table 1 below.

[0079] Table 1 below shows the polyamic acid composition, solid content, type and content of nano-silica of Examples 1-1 to 1-7 and Comparative Examples 1-1 to 1-4.

[0080] [Table 1]

[0081]

[0082]

[0083] Example 2. Polyamide cured product (polyimide film)

[0084] Example 2-1

[0085] The polyimide varnish prepared according to Example 1-1 was rotated at a high speed of 2,000 rpm to remove bubbles. Then, the degassed polyimide varnish was applied on a glass substrate (230 mm×230 mm, thickness: 0.55 mm).

[0086] Next, in a nitrogen atmosphere, curing was carried out under the conditions of 110° C. (20 minutes) → 150° C. (20 minutes) → 200° C. (20 minutes) → 300° C. (20 minutes) to obtain a film-type polyimide cured product (thickness of 20±1.0 μm or 26±1.0 μm).

[0087] Examples 2-2 to 2-7

[0088] Polyimide cured products were prepared in the same manner as in Example 2-1, except that the polyimide varnishes according to Examples 1-2 to 1-7 were respectively used instead of the polyimide varnish according to Example 1-1.

[0089] Comparative Examples 2-1 to 2-4

[0090] Polyimide cured products were prepared in the same manner as in Example 2-1, except that the polyimide varnishes according to Comparative Examples 1-1 to 1-4 were respectively used instead of the polyimide varnish according to Example 1-1.

[0091] Example 3. Polyimide coating material

[0092] Example 3-1

[0093] In a coating curing furnace, an electric wire including a polyimide coating material having a coating thickness of 110±10 μm was prepared by repeating the coating, drying and curing process of the polyimide varnish according to Example 1-1 on a square copper wire 20 to 28 times.

[0094] Examples 3-2 to 3-7

[0095] Wires including a polyimide coating layer were prepared in the same manner as in Example 3-1, except that the polyimide varnishes according to Examples 1-2 to 1-7 were respectively used instead of the polyimide varnish according to Example 1-1.

[0096] <Experimental example>

[0097] Experimental Example 1. Evaluation of physical properties of polyimide

[0098] (1) Pulse durability

[0099] According to IEC-60851-5, the pulse durability was determined by connecting the film-type polyimide cured products (thickness 26±1.0 μm) of the examples and comparative examples to a fixture, applying an AC 1.5 kV voltage (frequency 60 Hz), and measuring the time until a leakage current of 5 mA or more was detected. The results are shown in Table 2 below.

[0100] (2) Haze

[0101] The haze of the polyimide varnish or film-type polyimide cured product (thickness of 20±1.0 μm) of the examples and comparative examples was measured using a HunterLab device according to ASTM E308. The results are shown in Table 2 or Table 3 below.

[0102] [Table 2]

[0103]

[0104]

[0105] [Table 3]

[0106]

[0107]

[0108] As can be seen from Table 3, by using nano-silicon dioxide with a water content of less than 0.5wt%, the polyimide film of the present invention has significantly better pulse durability characteristics than Comparative Examples 2-1 and 2-2. In addition, Examples 2-1 to 2-7 show significantly improved pulse durability characteristics by including 6wt% to 20wt% of nano-silicon dioxide relative to the solid content of the polyimide, but Comparative Example 2-3, whose content is outside the above range, shows very low pulse durability characteristics of less than 300 minutes, and Comparative Example 2-4 cannot be measured because no film is formed.

[0109] In addition, according to Table 3 and Table 4, all polyimide varnishes and film-type cured products of the present invention can achieve low-level haze characteristics. Specifically, it was confirmed that the varnishes according to Examples 1-1 to 1-7 had a haze of 0.7% or less and the films according to Examples 2-1 to 2-7 had a haze of 0.8% or less. This shows that the nano-silica is not aggregated but uniformly dispersed.

[0110] Therefore, the present invention provides a polyimide varnish comprising a high content of nano-silica with a certain range of water content to have excellent physical properties such as haze, and also provides a polyimide cured product that achieves excellent pulse durability by using the polyimide varnish while also having excellent physical performance characteristics such as haze.

[0111] The polyimide varnish of the present invention can have excellent physical properties, such as haze, by including a certain range of nano-silica having a certain range of water content, while having excellent pulse durability.

[0112] The present invention may also have excellent use as a conductor coating for electric vehicle (EV) windings.

[0113] In the specification, details that can be fully recognized and inferred by those skilled in the art to which the present invention belongs are omitted, and in addition to the specific embodiments described in this specification, various modifications can be made within the scope of not changing the technical spirit or basic configuration of the present invention. Therefore, the present invention can be implemented in other ways that can be understood by those skilled in the art, rather than the specific description and examples herein.

Claims

1. A polyimide varnish comprising: polyamic acid and nano-silicon dioxide, wherein the nano-silicon dioxide accounts for 5wt% to 23wt% relative to the solid content of the polyamic acid, and the water content of the nano-silicon dioxide is less than 0.5wt%.

2. The polyimide varnish according to claim 1, wherein the nano silicon dioxide is surface-modified with an organosilane.

3. The polyimide varnish according to claim 2, wherein the organosilane of the nano-silicon dioxide surface-modified with the organosilane comprises one or more selected from the group consisting of methyltrimethoxysilane, hexamethyldisiloxane, n-octyltrimethoxysilane, n-octyltriethoxysilane, isooctyltrimethoxysilane, dodecyltrimethoxysilane, octadecyltrimethoxysilane, propyltrimethoxysilane, n-hexyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-(methacryloxy)propyltriethoxysilane, 3-(methacryloxy)propylmethyldimethoxysilane, 3-(acryloxypropyl)methyldimethoxysilane, 3-(methacryloxy)propyldimethylethoxysilane, styrylethyltrimethoxysilane, Methoxysilane, phenyltriethoxysilane, triethoxy-p-tolylsilane, vinylmethyldiacetoxysilane, vinyldimethylethoxysilane, vinylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, vinyltriisopropoxysilane, vinyltriphenoxysilane, vinyltri-tert-butoxysilane, vinyltri(isobutoxy)silane, vinyltriisopropenyloxysilane, vinyltri(2-methoxyethoxy)silane, N,N-diisopropylethylaminophenyltrimethoxysilane, glycidoxypropyltrimethoxysilane (GPTMS), 3-aminopropyltrimethoxy-silane (APTMS), phenyltrimethoxysilane (PTMS) and N-phenyl-3-aminopropyltrimethoxysilane (PAPTES).

4. The polyimide varnish according to claim 3, wherein the nano-silica surface-modified with an organosilane is obtained by combining a compound containing at least one phenyl group at the terminal and a compound containing at least one amine group, hydroxyl group, sulfhydryl group or epoxy group at the terminal on the surface of the nano-silica. 5 . The polyimide varnish according to claim 4 , wherein the compound containing at least one phenyl group at the terminal is phenyltrimethoxysilane (PTMS) and N-phenyl-3-aminopropyltrimethoxysilane (PAPTES).

6. The polyimide varnish according to claim 4, wherein the compound containing at least one amine group, hydroxyl group, mercapto group or epoxy group at a terminal is glycidoxypropyltrimethoxysilane (GPTMS) or 3-aminopropyltrimethoxysilane (APTMS). The polyimide varnish according to claim 1 , wherein the nano-silicon dioxide has an average particle size of 1 nm to 200 nm. 8 . The polyimide varnish according to claim 1 , wherein the polyamic acid has a solid content of 10 wt % to 50 wt %. 9 . The polyimide varnish according to claim 1 , wherein the polyamic acid comprises a dianhydride monomer and a diamine monomer as polymerization units.

10. The polyimide varnish according to claim 9, wherein the dianhydride monomer comprises at least one selected from the group consisting of pyromellitic dianhydride (PMDA), biphenyltetracarboxylic dianhydride (BPDA), benzophenonetetracarboxylic dianhydride (BTDA), oxydiphthalic anhydride (ODPA), diphenylsulfone-3,4,3',4'-tetracarboxylic dianhydride (DSDA), bis(3,4-dicarboxyphenyl)sulfide dianhydride, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,3,3',4'-benzophenonetetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride 1,4-bis(3,4-dicarboxyphenoxy)phthalic dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)phthalic dianhydride, 2,2-bis[(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, and 4,4'-(2,2-hexafluoroisopropylidene)diphthalic dianhydride.

11. The polyimide varnish according to claim 9, wherein the diamine monomer comprises at least one selected from the group consisting of 1,4-diaminobenzene (PPD), 4,4'-diaminodiphenyl ether (ODA), 2,2-diaminophenoxyphenylpropane (BAPP), m-phenylenediamine, 3,3'-dimethylbenzidine, 2,2'-dimethylbenzidine, 2,4-diaminotoluene, 2,6-diaminotoluene, 3,5-diaminobenzoic acid (DABA), 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl (m-tolidine), 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenylmethane , 3,3'-dicarboxy-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, 4,4'-diaminobenzanilide, 3,3'-dimethoxybenzidine, 2,2'-dimethoxybenzidine, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone, 3,3'-diamino-4,4'-dichlorobenzophenone, 3,3'-diamino-4,4'-dichlorobenzophenone, Dimethoxybenzophenone, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 2,2-bis(3-aminophenyl)propane, 2,2-bis(4-aminophenyl)propane, 2,2-bis(3-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 3,3'-diaminodiphenyl sulfoxide, 3,4'-diaminodiphenyl sulfoxide, 4,4'-diaminodiphenyl sulfoxide, 1,3-bis(3-aminophenyl)benzene, 1,3-bis(4-aminophenyl)benzene, 1,4-bis(3-aminophenyl)benzene, 1,4-bis(4-aminophenyl)benzene, 1,3-bis(4-aminophenyl)benzene, 1,3-bis(3-aminophenoxy)benzene (TPE-R), 1,4-bis(3-aminophenoxy)benzene (TPE-Q), 1,3-bis(3-aminophenoxy)-4-trifluorotoluene, 3,3'-diamino-4-(4-phenyl)phenoxybenzophenone, 3,3'-diamino-4,4'-bis(4-phenylphenoxy)benzophenone, 1,3-bis(3-aminophenylene sulfide)benzene, 1,3-bis(4-aminophenylene sulfide)benzene, 1,4-bis(4-aminophenylene sulfide)benzene, 1,3-bis(3-aminophenyl sulfone)benzene, 1,3-bis(4-aminophenyl sulfone)benzene, 1,4-bis(4-aminophenyl sulfone)benzene, 1,3-bis[2-(4-aminophenyl)isopropyl]benzene, 1,4-bis[2-(3-aminophenyl)isopropyl]benzene, 1,4-Bis[2-(4-aminophenyl)isopropyl]benzene, 3,3'-bis(3-aminophenoxy)biphenyl, 3,3'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, bis[3-(3-aminophenoxy)phenyl]ether, bis[3-(4-aminophenoxy)phenyl]ether, bis[4-(3)-aminophenoxy)phenyl]ether, bis[4-(4-aminophenoxy)phenyl]ether, bis[3-(3 bis[3-(4-aminophenoxy)phenyl]ketone, bis[4-(3-aminophenoxy)phenyl]ketone, bis[4-(4-aminophenoxy)phenyl]ketone, bis[3-(3-aminophenoxy)phenyl]sulfide, bis[3-(4-aminophenoxy)phenyl]sulfide, bis[4-(3-aminophenoxy)phenyl]sulfide, bis[4-(4-aminophenoxy)phenyl]sulfide, bis[3-(3-aminophenoxy)phenyl]sulfide, bis[4-(4-aminophenoxy)phenyl]sulfide, bis[3-(3-aminophenoxy)phenyl]sulfone, bis[3-(4-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[3-(3-aminophenoxy)phenyl]methane, bis[3-(4-aminophenoxy)phenyl]methane, bis[4-(3-aminophenoxy)phenyl]methane, bis[4-(4-aminophenoxy)phenyl]methane, 2,2-bis[3-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(4-aminophenoxy)phenyl]propane, 2,2 -bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[3-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane and 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane. 12 . The polyimide varnish according to claim 1 , wherein the polyamic acid comprises pyromellitic dianhydride (PMDA) and 4,4′-diaminodiphenyl ether (ODA) as polymerization units. 13 . The polyimide varnish according to claim 1 , wherein the polyimide varnish further comprises an organic solvent.

14. The polyimide varnish according to claim 13, wherein the organic solvent comprises at least one selected from the group consisting of N-methylpyrrolidone (NMP), N,N'-dimethylformamide (DMF), N,N'-diethylformamide (DEF), N,N'-dimethylacetamide (DMAc), dimethylpropionamide (DMPA), N,N-diethylacetamide (DEAc), dimethyl sulfoxide (DMSO), 3-methoxy-N,N-dimethylpropionamide (KJCMPA), p-chlorophenol, o-chlorophenol, γ-butyrolactone (GBL), diethylene glycol dimethyl ether, and naphthalene. 15 . The polyimide varnish according to claim 13 , wherein the organic solvent further comprises a modifier containing a hydroxyl group (OH) or an amine group (NH). 16 . The polyimide varnish according to claim 1 , wherein the polyimide varnish has a haze of 1.5% or less. 17 . A polyimide cured product obtained by curing the polyimide varnish according to claim 1 . 18 . The polyimide cured product according to claim 17 , wherein the polyimide cured product has a haze of 1.5% or less. 19 . The polyimide cured product according to claim 17 , wherein the polyimide cured product has a pulse durability of 300 minutes or more, the pulse durability being a time for an insulating material to withstand a specific voltage according to IEC-60851-5.

20. A polyimide coating material comprising the polyimide varnish according to claim 1.